STRATEGI KOMUNIKASI KEMITRAAN DALAM PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS ENERGI TERBARUKAN DAN SUMBER DAYA LOKAL - Lasria Sinambela (PT Sanagi Edu Konsultan, 2025)
Renewable energy is not merely a technical solution to address disparities in electricity access; it also serves as a communication arena that connects communities, governments, and development partners. This study explores the communication strategies within partnerships implemented by the People-Centered Business and Economic Initiatives Foundation (IBEKA) to empower rural communities through renewable energy. Using a qualitative case study approach, the research reveals that program success is shaped not only by technological availability but also by participatory communication that fosters ownership, trust, and collaboration among stakeholders. Through community dialogues, training, and social organization, community participation increased by 75%, while household incomes rose by approximately 50% through social business models. These findings highlight that communication is not a supporting element, but the very foundation bridging technology, policy, and local needs. Practically, this study offers implications for academics, policymakers, and non-profit organizations to position communication as a central strategy in designing sustainable community empowerment programs based on renewable energy.